Multi-field energy release characteristics during shell-encapsulated Al/PTFE energetic powder deflagration reaction - Enling Tang; Jiameng Hou; Ruizhi Wang; Yafei Han; Chuang Chen; Mengzhou Chang; Kai Guo; Liping He (Case Studies in Thermal Engineering)
With the evolution of battlefield environments and the shifting nature of mission objectives, there is a growing demand for non-thermal energy release from energetic materials. Characterizing the multi-physical-field response parameters and energy release behaviors of these materials during reaction processes has become critically important. In this study, Al/PTFE mixed energetic powders (26.5 %/73.5 % by mass) were investigated. The heat release of the Al/PTFE energetic powder was measured using an oxygen bomb calorimeter, and a self-constructed multi-field parameter testing system was employed to monitor various response parameters—including overpressure, acoustic signals, light flash, and electromagnetic emissions—during the deflagration of shell-encapsulated Al/PTFE energetic powders under varying charge mass and charge density conditions in a confined environment. The multi-field energy release characteristics were systematically analyzed. Experimental results demonstrated that the shell-encapsulated Al/PTFE energetic powders exhibited distinct multi-field responses. The intensities of overpressure, sound, light flash, and electromagnetic emissions increased with the charge mass but decreased as the charge density increased within the range of 0.6–0.8 g/cm3. The maximum energy released during the combustion reaction reached 14.3284 kJ/g. These findings provide a theoretical foundation for the design, performance optimization, and safety enhancement of high-energy materials, and hold potential application value in military engineering, aerospace propulsion, and disaster prevention systems. Furthermore, they lay the groundwork for future research on the influence of shell material and energetic particle sizes on multi-field energy release behavior.